2023
DOI: 10.1177/18632521231156435
|View full text |Cite
|
Sign up to set email alerts
|

Readability assessment of patient educational materials for pediatric spinal conditions from top academic orthopedic institutions

Abstract: Background: The Internet has become a popular source of health information for patients and their families. Healthcare experts recommend that the readability of online education materials be at or below a sixth grade reading level. This translates to a standardized Flesch Reading Ease Score between 81 and 90, which is equivalent to conversational English. However, previous studies have demonstrated that the readability of online education materials of various orthopedic topics is too advanced for the average p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Although this change did lower the grade level of these resources, the average of the scores was still well above the recommended level of eighth grade. Michel et al 24 found similar results when examining webpages for pediatric spinal conditions. The lower readability among webpages describing spinal conditions may be because of the complexity of spinal conditions and their treatment.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…Although this change did lower the grade level of these resources, the average of the scores was still well above the recommended level of eighth grade. Michel et al 24 found similar results when examining webpages for pediatric spinal conditions. The lower readability among webpages describing spinal conditions may be because of the complexity of spinal conditions and their treatment.…”
Section: Discussionmentioning
confidence: 68%
“…The lower readability among webpages describing spinal conditions may be because of the complexity of spinal conditions and their treatment. 24,33…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations